EXPLORING MAHTEMATICS THROUGH ORIGAMI - Gupta, O.P. (SCHOOL SCIENCE, 2013)
Origami literally translates as Ori (folding) gami (paper). It could be used as a valuable method for developing vital skills in mathematics. It is not just a game. All general principles of mathematics are involved in creation of shapes through origami. It can be easily expressed with the help of folding. By using simple square sheets of paper, students can use their imagination and creativity. Difficult and abstract mathematical concepts can be explained in an interesting manner through origami. The basic tool of origami is a simple sheet of square paper. We will fold a square sheet of paper in any way and begin to see the unlimited possibilities that the square has to offer. Why is the square sheet of paper used in exploring mathematics in folding? The square sheet of paper used due to its some peculiar properties: 1. It has all properties of quadrilateral, parallelogram, trapezium and rectangle. 2. Its diagonals are equal in length and bisect each. 3. Its diagonal divides the shape into two isosceles right triangles. 4. The interesting point of diagonals lies on angle bisector of all angles and perpendicular bisector of all sides. 5. All its exterior angles and interior angles are equal.